Focus on suburbia: a design project where the villa suburbia and its people play a role in sustainable change - Khezri, Pouya (My University, 2022)
Villa suburbs are common sight in the modern city, this is also true to the Swedish urban fabric. There is great demand for these areas, high standard of living with comforts of large space, calm neighborhoods, and high level of privacy. Yet these neighborhoods are seldom in focus in the discussion of urban change, a rhetoric that these neighborhoods are already good and don’t need change. They do like many other places bring bad qualities. Issues like inefficient land use, high consumption lifestyles, car dependency, segregation of socioeconomic groups, and weak communities. Focus on the villa suburb can in fact contribute to the discourse of more sustainable cities. This thesis brings ways to see how the Swedish villa suburbia can inhabit sustainable change through design. To add to the current physical environment in such a way sustainable changes can occur. It requires an understanding of why the villa suburbs are still increasingly attractive, to understand not only the issues but also the qualities of the villa suburb so that elements are sustained while bringing further qualities. The case of this thesis is the neighborhood of Solängen in the city of Mölndal. A study of the site and interviews with inhabitants and organizations have been done so the design is one with an understanding of the area according to locals. Together with theory a process occurs where research through design reflects in three design concepts that is applied to a block in the center of Solängen. The design concepts being densifying with restructuring of floor plans in villas, densifying with additions of new building units on property, placemaking by creating space for local community to meet, interact and share resources. The result is a proposal that could bring opportunity of solving larger issues of suburbia. It can combat urban sprawl, bringing efficient land and resource use with densification and more sharing economy. Also combatting segregation and isolation with tighter communities and a diversity of new people through a diverse housing stock. The result can contribute to the discourse of the suburbs role towards a sustainable future.
Keywords: Villa suburb, densifying, placemaking, diversity, community